Islam Ramah di Pesantren: Islami, Tarbawi dan Ma’hadi - Hidayat Aji Permana; Ainul Yakin (Fakta: Jurnal Pendidikan Agama Islam, 2021)
The hierarchical values can be grouped into two groups, namely: divine values which consist of ubudiyah values and mu'amalah values, then human ethical values which consist of rational, social, individual, biovistic, economic values. politics, and aesthetic values. This study aims to explain what Islamic values are like, describe the components and describe the implementation of the cultivation of Islamic, tarbawi and Ma'hadi values at the TMI Al-Amien Prenduan Islamic Boarding School. In this study, researchers used a qualitative research approach. As for the research data collection, namely by using interview instruments, observation and documentation. Meanwhile, in the data analysis, the researcher brought together the field data with the theory as a surgical knife. The results showed that the Islamic, Tarbawi and Ma'hadi values that were rooted and thrived in the TMI Al-Amien Prenduan Islamic Boarding School were stuck in all the activities and life in them, as well as the components that moved and ran the system, consisting of, Kiai, Ustad, Santri and guidebooks, where the three complement each other, fixing the preservation of the existing system, and the last is the implementation of these values, namely by instilling these values in every individual who lives in the uswah hasanah lodge, akhlakul karimah and religious values other.